Systematic description of the internet of things: A bibliometric analysis - Mohd Izham, Mohd Jaya; Mohd Faizal, Ab Razak; Eh Phon, Danakorn Nincarean; Syifak Izhar, Hisham; Ahmad Firdaus, Zainal Abidin (Little Lion Scientific, 2022)
The explosive progress of the Internet of Things (IoT), such as smart watches, medical implants, and smart refrigerators, has empowered researchers to view these developments of science and technology from the research perspective. The breakthrough of accelerated technologies has helped to reshape global research patterns in IoT. Despite the many articles published in research, there is, however, still a lack of bibliometric reports that demonstrate the comprehensive research patterns of the IoT. This study seeks to assess the world’s research activities on the IoT by observing the gaps through a thorough research pattern of the IoT research practices. The analysis of more than 1000 articles that were published between 2009 to 2019 in the ISI Web of Science (WoS) database was performed through the bibliometric approach. The outcome showed the global research pattern of the activities in the following forms: notable journals, foremost articles, research areas, influential institutions, most prolific countries, authors productivity, keywords and network collaborations. A closer inspection of the bibliometric analysis also showed that a comprehensive analysis is significant for measuring the degree of activity in research patterns.